2021
DOI: 10.3390/md19030163
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Astaxanthin-Loaded Microparticles Modulates TGFβ Production and Intracellular ROS Levels in J774A.1 Macrophages

Abstract: Radiation-induced fibrosis is a serious long-lasting side effect of radiation therapy. Central to this condition is the role of macrophages that, activated by radiation-induced reactive oxygen species and tissue cell damage, produce pro-inflammatory cytokines, such as transforming growth factor beta (TGFβ). This, in turn, recruits fibroblasts at the site of the lesion that initiates fibrosis. We investigated whether astaxanthin, an antioxidant molecule extracted from marine and freshwater organisms, could help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Full details concerning the synthesis of ASX-loaded microparticles along with their complete biochemical and biological characterization have been given in reference [ 11 ]. In this work we used the same preparations and in this section we describe new data concerning PTX and its interactions with ASX microparticles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full details concerning the synthesis of ASX-loaded microparticles along with their complete biochemical and biological characterization have been given in reference [ 11 ]. In this work we used the same preparations and in this section we describe new data concerning PTX and its interactions with ASX microparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we showed that ASX microparticles were not cytotoxic for J774A.1 macrophage cells [ 11 ]. To the best of our knowledge no information is available on the safety of PTX in this cell system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations